NOTARY FUNCTION IN TRANSFER OF SUBSIDIZED HOUSE OWNERSHIP CREDIT - Mahreza, Safna Wira Agisna Irnadya; Gozali, Djoni Sumardi (JILPR Journal Indonesia Law and Policy Review, 2025)
Notary Notaries as public officials have an important role in ensuring legal certainty and protection in every agreement, including in the transfer of subsidized home ownership credit. Many credit transfers are carried out underhand, without the consent of the bank and without an authentic deed from the notary, thus creating legal uncertainty for new debtors who take over credit obligations. This study uses a normative legal research method with a statute approach, a conceptual approach, and a legal theory approach. The data used are secondary data in the form of primary, secondary, and tertiary legal materials which are analyzed qualitatively with descriptive analysis techniques. The results of the study show that: Notaries have the authority to make authentic deeds in the transfer of home ownership credit as regulated in Article 15 paragraph (1) of Law Number 2 of 2014 concerning Amendments to Law Number 30 of 2004 concerning the Position of Notary (UUJN). Credit transfers carried out without a notarial deed and without the bank's approval are not legally recognized and are only considered as underhand agreements that have limited evidentiary power, and the failure to involve a notary in the credit transfer process can have legal consequences for the parties, especially for new debtors who do not have a clear legal standing, and are at risk of losing their rights to the house they have paid for.